The impact of Inuit Qaujimajatuqangit on formal education in Nunavut - Ayres, Matthew (2012)
Long before the introduction of a western-style formal education for the Inuit of Canada’s north, the people learned everything they needed to know from their immediate and extended family units. The goal of education for Inuit at that time was simple: learn the skills needed to survive. The current goal of education in Canada is similar, though ‘survival’ has a new context where governments and educators focus more on how to prosper and succeed (in addition to being able to survive). There have been many fundamental shifts in the methodology behind educating Inuit students but each paradigm has intended to better prepare children how to survive in the modern world. In 2012, for example, there is more of a focus on Calculus than on skinning caribou and students learn how to read sheet music instead of watching elders beat a sealskin drum and mimicking the rhythm. Curriculum focuses on scientific or historical facts rather than myths or legends to explain how the world works. This thesis examines the latest two paradigms in educational curricula in the territory now known as Nunavut. In 1999, the territory of Nunavut came into effect when the Nunavut Act was proclaimed. Before this, the area now known as Nunavut was part of a much larger and more culturally diverse Northwest Territories. In the years leading up to 1999, plans began to take shape that would lead to the separation of Inuit inhabited lands. Inuit desired a system of government that reflected their own distinct culture, and enabled them to make decisions and policies for those living within their boundaries. The Inuit Qaujimajatuqangit (more easily remembered as IQ), a set of principles that refer to traditional Inuit knowledge and knowledge gathering, is a key example. The new government of Nunavut introduced IQ principles to guide decisions, policies and set values that would create a government that was truly representative of the people it served. Prior to this, the Northwest Territories used a system of education and pedagogy that was adopted ...